Mice Immunized with IgG Anti-Sheep Red Blood Cells (SRBC) Together With SRBC Have a Suppressed Anti-SRBC Antibody Response but Generate Germinal Centers and Anti-IgG Antibodies in Response to the Passively Administered IgG - Bergström, Joakim J. E.; Heyman, Birgitta (Frontiers in Immunology, 2017)
Antigen-specific IgG antibodies, passively administered together with large particulate antigens such as erythrocytes, can completely suppress the antigen-specific antibody response. However, the mechanism behind has been elusive. Herein, we made the surprising observation that mice immunized with IgG anti-SRBC (sheep red blood cells) and SRBC, in spite of a severely suppressed anti-SRBC response, have a strong germinal center (GC) response. This occurred regardless of whether the passively administered IgG was of the same allotype as that of the recipient or not. Six days after immunization, the GC size and the number of GC B cells were higher in mice immunized with SRBC alone than in mice immunized with IgG and SRBC, but at the other time points these parameters were similar. GCs in the IgG-groups had a slight shift towards dark zone B cells six days after immunization and towards light zone B cells ten days after immunization. The proportions of T follicular helper (TFH) and T follicular regulatory (TFR) cells were similar in the two groups. Interestingly, mice immunized with allogeneic IgG anti-SRBC together with SRBC mounted a vigorous antibody response against the passively administered suppressive IgG. Thus, although their anti-SRBC response was almost completely suppressed, an antibody response against allogeneic, and probably also syngeneic, IgG developed. This most likely explains the development of GCs in the absence of an anti-SRBC antibody response.